ARKEOLOGI PULAU TERDEPAN: TINJAUAN POTENSI PURBAKALA DI PULAU SELARU MALUKU TENGGARA BARAT (Archaeology of Outermost Island: The Potential Overview in Selaru Island West Southeast Moluccas Indonesia) - Marion Ririmasse (BALAI ARKEOLOGI PAPUA, 2016)
Selaru Is one of the 92 outermost Islands In Indonesia. Geographically located in the TanlmbarArchipelago, Selaru is one of the southeastemmost island of Indonesia which is closely located to Australia. A condtion that present the strategic value in terms of politics and academics for this area. Unfortunately, despite the importance of this Island, very limited archaeological and cultural historical study has been conducted In Selaru. This paper is a prelimenary overview of archaeological potential in one of the country frontline. The reconaissance survey has been adopted as an approach in this research. The results shows that Selaru is a potential region to be developed in the framework of archaeology and cultural history of the region. Includes, the cultural study to develop the border area of Indonesia. AbstrakPulau Seiaru adalah salah satu dan 92 pulau terdepan di Indonesia. Terletak di Kepulauan Tanlmbar; Selaru menjadl salah satu pulau terselatan Nusantara yang paling dekat dengan daratan Australia. Hal mana memberi nilai strategis secara politis dan akademis bagi wilayah ini. Meski dengan nilai penting sedemikian, belum banyak perhatian dari studi arkeologi dan sejarah budaya bagi Pulau Selaru. Makalah ini merupakan tinjauan awal atas potensi arkeologi yang ada di salah satu wilayah teras negara ini. Pendekatan peneiitian dilakukan dengan menggunakan metode survei penjajakan. Hasil studi menemukan bahwa Selaru memiliki potensi dalam kerangka studi arkeologi dan sejarah budaya kawasan. Termasuk dalam kaitan dengan kajian budaya untuk pengembangan kawasan perbatasan.